Supported housing for people with Down's syndrome. (14th June 2013) - Cumella, Stuart; Heslam, Sheila
<x xml:space="preserve">Abstract</x> Accessible summary This is about people with Down's syndrome who live in supported housing. Their parents said that they liked the help given by support staff to people with a learning disability. They thought more help was needed with managing money and finding a job. People had to wait a long time before they could get a place in supported housing. Parents carried on giving help to their sons and daughters even after they had gone into supported housing. Parents helped most with things like managing money and dealing with problems. This means that people who live in supported housing who do not have parents find life more difficult. Summary There has been limited research on the attitudes of family carers and the part they play in helping people with a learning disability choose accommodation. A postal questionnaire was sent to family carers of people with Down's Syndrome, to identify their attitudes to supported living, their experience of the application process, and the support they provided to residents. It was found that main family carers of people with Down's Syndrome in supported living were generally satisfied with the housing and support provided, particularly with respect to activities of daily living. There was less satisfaction with the help received with managing finance and employment. There had been a mean of 2 years delay between application and securing accommodation. The large number of people providing care at home who wished their family‐member to move into supported living suggests that there is a large unmet need for this type of accommodation. Almost all family carers continued to provide support after participants moved into supported living, particularly with more complex tasks such as financial management, and with responding to crises and ill‐health. This indicates that people with a learning disability in supported living who do not have active contact with their family may be vulnerable financially and less likely than others to receive help at times of crisis. The proportion of residents in supported living who experience such problems will increase as family carers die or otherwise become too infirm to continue to provide support.